Bibliometric Analysis of Research Output on Smartphone Addiction from 2000 to 2023 - Kumar, Kutty; Pitla, Raja Suresh Kumar; Siva, Balaraman (Journal of Data Science, Informetrics, and Citation Studies)
The utilization of mobile phones has been steadily and rapidly increasing in recent years. Research publications are crucial for keeping information up to date. Recently, there has been a growing study endeavor focused on the utilization of mobile phones. This research seeks to uncover the global growth pattern of Smartphone addiction research, the contributions made to the area, the current subjects that are trending in the field, the primary themes that dominate the field, and the behavioral addiction patterns in nations that are influential in this field. A bibliometrics analysis was conducted using 1673 publications obtained from the PubMed database. These publications were sourced from 450 journals and books and covered the period from 2000 to 2023. Based on the study's findings, the literature on Smartphone addiction has had a notable increase since 2011, with the highest growth rate of articles being 15.73% in 2022. The Journal of Behavioral Addictions and Addictive Behaviors are the most prolific journals in the discipline, with 159 publications each. The Catholic University of Korea has the most significant collaboration with 147 published papers. The most productive countries in terms of publications are Korea, with 111 publications, and China, which has the highest number of publications. The current focus of discussion in the field of Smartphone addiction revolves around the utilization of addictive behaviors and internet usage. This study conducted a thorough examination of the existing knowledge in the area of Smartphone addiction and offered a comprehensive viewpoint on the subject. Additionally, this study presents potential avenues for future investigation.
Keywords: Bibliometric Analysis; Research Output; Smartphone; Addiction; Dendographam; Bibliometrics; India.